Dobra administracja : kadry i motywacja, czyli co mówią urzędnicy i obywatele - oczekiwania i rzeczywistość - Wysocki, Sławomir (Good Administration : Personnel and Мotivation : What Officials and Citizens Say - Expectations vs. Reality, 2008)
The paper discusses a problem of increasing dissatisfaction among public administration personnel and illustrates it by data concerning various regions. It presents opinions of citizens, officials, informations on the structure of the administration and employment. The author points out that the requirements of internal administration (including the need to create strategies of action or so-called rationalization of public expenses) and social requirements (including giving real information to citizens friendly attitude, clearness of procedures) force systemic actions which improve the level of governance in administration (or- as some politicians and experts say "quality of governance"). (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 167-178